Impact of body mass index on outcome of adult cardiac surgery - Qabaha, Anan Hasan; Al-Fawares, Safwan Galeb; Alqaisi, AbdaAllah Ibrahim; Alshobaki, Wael Ibrahim; Al-Adwan, Rawand Hayel; Mohd, Ashraf Fadel; Al-Aqqad, Nisrein Mousa (International Journal of Advances in Medicine, 2024)
Background: The objectives of study were to determine the incidence of overweight and obesity in adult cardiac surgical patients, and to evaluate the impact of BMI on outcome from cardiac surgery. Methods: Retrospective observational analysis of data of adult cardiac surgery at Queen Alia heart institute (QAHI) in the period of time between September 2023 and February 2024. Patients’ data were recorded and analysed. Patients were divided in categories according to the world health organisation (WHO) body mass index (BMI) classification. The WHO BMI categories were compared regarding their pre-operative, intra-operative and post-operative characteristics. Recovery parameters such as extubation time, length of ICU stay, length of hospitalisation and mortality were also compared between normal weight, overweight and obesity categories. Ethical committee approval obtained. Results: Data from 141adult cardiac surgical patients was analysed. Male patients were 115 (81.56%) and female patients were 26 (18.44%) with a male to female ratio of 4.4. Mean age of patients was 56.66 (SD 10.26). Majority of patients were obese (39%) and overweight (34%). The Incidence of diabetes in the normal weight category was 41.7%; while in the overweight category it increased to 58.4% and reached 60% in the obese category. The incidence of hypertension (75% in the overweight and 76.4% in the obese categories) increased with the increase of the BMI. Obese category had prolonged mean duration of hospitalisation (13 days); however, lower rates of re-opening and mortality. Conclusions: Most of the adult cardiac surgical patients in this study are obese and overweight. The overweight and obese patients had higher rates of hypertension, diabetes and ischaemic heart disease. Longer hospitalisation and lower mortality rates were noted in patients with higher BMI.